Double-dispersion silica sol for chemical mechanical polishing as well as preparation method and application of double-dispersion silica sol

By mixing the seeds of silicon sols of different particle sizes and processing them in an alkaline environment, a double-dispersed silica sol of 70~100 nm is prepared, which solves the problem of difficult preparation of large-particle size double-dispersed narrow-dispersed silica sols in the prior art, and achieves efficient grinding of copper and silica.

CN119797377APending Publication Date: 2025-04-11DINGZE (XIANTAO) NEW MATERIALS TECHNOLOGY CO LTD +3
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411805893.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The prior art is difficult to prepare a large-particle size double-dispersed narrow distribution silicon sol, which cannot meet the needs of modern layer planarization.

Method used

By mixing the first silicon sol seed with a particle size of 40~60 nm and the second silicon sol seed with a particle size of 40~70 nm, and adding active silicic acid to an alkaline environment, the particle size distribution is controlled to form a double dispersed silicon sol of 70~100 nm.

Benefits of technology

A double-dispersed silicon sol with narrow particle size distribution and uniform particle size distribution is achieved, and the grinding rate of copper and silica is improved, and it is suitable for semiconductor chemical mechanical polishing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119797377A_ABST
    Figure CN119797377A_ABST
Patent Text Reader

Abstract

The invention discloses a bi-dispersed silica sol for chemical mechanical polishing, the bi-dispersed silica sol is formed by growth of a first silica sol seed crystal with the particle size of 40-60 nm and a second silica sol seed crystal with the particle size of 40-70 nm, the particle size of the bi-dispersed silica sol is 70-100 nm, and the difference value between the DLS particle size mean value and the CPS particle size mean value of the bi-dispersed silica sol is 0-10 nm. The double-dispersed silica sol is narrow in particle size distribution, uniform in particle size distribution and high in product yield. The double-dispersion silica sol prepared by the invention can be used in the field of chemical mechanical polishing of semiconductors, and a polishing solution prepared by utilizing the double-dispersion silica sol has a relatively good removal rate on copper and silicon dioxide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of new materials, and more specifically, to a bidispersed silica sol for chemical mechanical polishing and a preparation method and application thereof. Background Art

[0002] Polishing liquid is an indispensable material for the semiconductor chip industry to planarize integrated circuits, and abrasives are the most important component of polishing liquid. Large-particle silica sol can increase the planarization rate, improve manufacturing efficiency and increase production capacity. The particle size distribution of silica sol has a greater impact on the planarization process. Small-particle particles play a very limited role in the planarization process, and large particles are easy to damage and scratch the chip surface. Therefore, chip planarization has very high requirements for the particle size distribution of abrasives.

[0003] Silica sol itself is a colloidal solution of colloidal dispersed particles of silicon dioxide in aqueous solution. It is a very important inorganic material with a wide distribution of particle size, ranging from 5 to 100 nm. Since there are a large number of hydroxyl groups on the surface of the silicon dioxide particles in the silica sol, it has good chemical activity, so silica sol is widely used in chemical industry, precision manufacturing, textile, papermaking, electronics and other fields. At present, the main preparation methods of silica sol are: elemental silicon hydrolysis method, silane coupling agent hydrolysis method, water glass ion exchange method, dispersion method, colloidal dissolution method. The most commonly used methods are elemental silicon hydrolysis method and water glass ion exchange method. The particle size synthesized by elemental silicon hydrolysis method is between 20 and 40 nm. The small particle size is difficult to meet the needs of planarization of some special layer chips.

[0004] Patent CN102432027B discloses a monodisperse, large-particle, high-stability acidic silica sol prepared by an ion exchange resin method and a preparation method thereof. The prepared silica sol has a particle size of up to 100 nm, but its silica sol particle size distribution is between 1 and 100 nm, which is difficult to meet the flattening requirements of modern layer making. Patent CN105883824B discloses a monodisperse large-particle silica sol prepared by an ion exchange resin method, and the particle size can reach up to 100 nm, but it is monodisperse and cannot meet the requirements of some special dual processes.

[0005] Therefore, how to prepare silica sol with large particle size, double dispersion and narrow distribution has become a demand of some special process industries, and it is also a difficult problem facing the silica sol industry. Summary of the invention

[0006] An object of the present invention is to solve at least the above problems and to provide at least the advantages which will be described hereinafter.

[0007] Another object of the present invention is to provide a bidisperse silica sol, wherein the particle size of the bidisperse silica sol is 70-100 nm, and the difference between the DLS particle size mean and the CPS particle size mean of the bidisperse silica sol is between 0-10 nm. This indicates that the bidisperse silica sol has a narrow particle size distribution and a uniform particle size distribution, and can be used in the field of chip chemical mechanical polishing, and has a high removal rate for copper and silicon dioxide.

[0008] In order to achieve these purposes and other advantages according to the present invention, the first aspect of the present invention provides a bidisperse silica sol for chemical mechanical polishing, wherein the bidisperse silica sol is formed by mixed growth of a first silica sol seed with a particle size of 40 to 60 nm and a second silica sol seed with a particle size of 40 to 70 nm, the particle size of the bidisperse silica sol is 70 to 100 nm, and the difference between the DLS particle size mean and the CPS particle size mean of the bidisperse silica sol is between 0 and 10 nm.

[0009] A second aspect of the present invention provides a bidisperse silica sol, which is formed by mixed growth of a first silica sol seed with a particle size of 40-60 nm and a second silica sol seed with a particle size of 40-70 nm, the particle size of the bidisperse silica sol is 70-100 nm, and the difference between the DLS particle size mean and the CPS particle size mean of the bidisperse silica sol is between 0-10 nm.

[0010] Preferably, the bidisperse silica sol is prepared by mixing a first silica sol seed crystal with a particle size of 40-60 nm and a second silica sol seed crystal with a particle size of 40-70 nm, and then adding a pH regulator and dropping active silicic acid thereto to grow.

[0011] Preferably, the first silica sol seed crystal is prepared by adding a pH regulator and dropping active silicic acid for a first time length to an initial silica sol seed crystal with a particle size of 20 to 35 nm to grow; The second silica sol seed crystal is prepared and grown by adding a pH regulator and dropping active silicic acid for a second time length into an initial silica sol seed crystal with a particle size of 20-35 nm.

[0012] Preferably, the CPS particle size peaks measured for the bidisperse silica sol are respectively recorded as Q1 and Q2, and Q1 / Q2 is 0.65-0.80.

[0013] The third aspect of the present invention provides a method for preparing a bidisperse silica sol, comprising the following steps: mixing a first silica sol seed with a particle size of 40 to 60 nm and a second silica sol seed with a particle size of 40 to 70 nm, adding a pH adjuster, and dripping active silicic acid to obtain a bidisperse silica sol with a particle size of 70 to 100 nm.

[0014] Preferably, the first silica sol seed crystal is prepared by adding a pH regulator and dropping active silicic acid for a first time length to an initial silica sol seed crystal with a particle size of 20 to 35 nm to grow; The second silica sol seed crystal is prepared by adding a pH regulator and dropping active silicic acid for a second time length to an initial silica sol seed crystal with a particle size of 20 to 35 nm to grow; The initial silica sol seed crystals are formed by dropping active silicate into an alkaline base solution, and the particle size of the initial silica sol seed crystals is 20-35 nm; The preparation method of the alkaline base liquid is as follows: adding 1-10 wt% of a pH regulator, adjusting the pH range to 10.5-12, heating to 90-100° C., and keeping the temperature for 1-5 hours to obtain; The preparation method of the active silicate is as follows: using water glass as a raw material, and diluting it after passing through a cation exchange resin; The reaction temperature when preparing the initial silica sol seed crystal, the first silica sol seed crystal, the second silica sol seed crystal and the bidisperse silica sol is 90-100°C.

[0015] Preferably, when preparing the initial silica sol seed crystals, the mass ratio of the alkaline base solution to the active silicic acid is 1:(2-7); Preferably, when preparing the first silica sol seed crystals, the mass ratio of the initial silica sol seed crystals to the active silicic acid is 1:(2-10), and the pH is 11-12.5; Preferably, when preparing the second silica sol seed crystals, the mass ratio of the initial silica sol seed crystals to the active silicic acid is 1:(5-15), and the pH is 11-12.5; Preferably, when preparing the bidisperse silica sol, the mass ratio of the first silica sol seed and the second silica sol seed to the active silicic acid is 1:(2-8), the pH is 11-12.5, and the mass ratio of the first silica sol seed to the second silica sol seed is 1:(1-4).

[0016] Preferably, the drop rate of the active silicate is 1-20 g / min; Preferably, when preparing the initial silica sol seed crystals, the drop rate of the active silicic acid is 1-5 g / min; Preferably, when preparing the first silica sol seed crystal, the drop rate of the active silicic acid is 3-8 g / min; Preferably, when preparing the second silica sol seed crystal, the drop rate of the active silicic acid is 2-6 g / min; Preferably, when preparing the bidisperse silica sol, the dropping rate of the active silicic acid is 1-5 g / min.

[0017] Preferably, the pH regulator is one or more of sodium hydroxide, potassium hydroxide, sodium silicate, ammonia water, and tetrabutylammonium hydroxide.

[0018] A fourth aspect of the present invention provides a use of bidisperse silica sol in a polishing liquid for chemical mechanical polishing of copper and silicon dioxide.

[0019] The present invention has at least the following beneficial effects: 1. The present invention uses water glass as a raw material to prepare active silicate through ion exchange, and then drops the active silicate into an alkaline environment to prepare silica sol. By controlling the drop rate, the pH of the alkaline environment and the particle size and adopting a step-by-step growth process, a 70-100nm narrow distribution bidisperse silica sol can be stably produced. The particle size distribution is uniform and can be used in the field of semiconductor chemical mechanical polishing. 2. The difference between the DLS particle size mean and the CPS particle size mean of the bidisperse silica sol prepared by the present invention is between 0 and 10 nm, indicating that the bidisperse particle size distribution is concentrated, which is beneficial to improving the grinding rate of copper and silicon dioxide; 3. The peak value Q1 / Q2 corresponding to the CPS particle size diagram tested by the high-precision nanoparticle size analyzer is maintained between 0.65 and 0.80, which can play a role in adjusting the grinding selectivity of Cu and SiO2 while maintaining a high grinding rate.

[0020] Other advantages, objectives and features of the present invention will be embodied in part through the following description, and in part will be understood by those skilled in the art through study and practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is a CPS particle size diagram of the bidisperse silica sol of Example 1 of the present invention; Figure 2 This is a SEM image of the bidisperse silica sol of Example 1 of the present invention; Figure 3 This is a CPS particle size diagram of the bidisperse silica sol of Example 2 of the present invention; Figure 4 This is a SEM image of the bidisperse silica sol of Example 2 of the present invention; Figure 5 This is a CPS particle size diagram of the bidisperse silica sol of Example 3 of the present invention; Figure 6 This is a CPS particle size diagram of the bidisperse silica sol of Example 4 of the present invention; Figure 7 This is a CPS particle size diagram of the bidisperse silica sol of Example 5 of the present invention; Figure 8 This is a CPS particle size diagram of the silica sol of Comparative Example 1 of the present invention; Fig. 9This is a CPS particle size diagram of the silica sol of Comparative Example 2 of the present invention; Fig.10 This is the SEM image of the silica sol of comparative example 5 of the present invention. DETAILED DESCRIPTION

[0022] Hereinafter, the present invention will be described in detail.

[0023] The present invention provides a bidisperse silica sol, which is formed by mixed growth of a first silica sol seed with a particle size of 40-60 nm and a second silica sol seed with a particle size of 40-70 nm, the particle size of the bidisperse silica sol is 70-100 nm, and the difference between the DLS particle size mean and the CPS particle size mean of the bidisperse silica sol is between 0-10 nm.

[0024] In an embodiment of the present invention, the particle size of the bidisperse silica sol is 70-100 nm. The silica sol of the present invention can improve the planarization rate, has a good polishing rate for specific substances, and can meet the polishing requirements of multiple processes. The difference between the DLS particle size mean and the CPS particle size mean of the bidisperse silica sol of the present invention is between 0 and 10 nm, indicating that the bidisperse silica sol has a narrow particle size distribution and a concentrated particle size distribution, which can effectively improve the polishing rate of copper and silicon dioxide.

[0025] In an embodiment of the present invention, the bidisperse silica sol is formed by growing the initial silica sol seed with a particle size of 20 to 35 nm to form the first silica sol seed with a particle size of 40 to 60 nm and the second silica sol seed with a particle size of 40 to 70 nm, and then the first silica sol seed and the second silica sol seed are mixed and then grown again. The first silica sol seed and the second silica sol seed are prepared and grown from the initial silica sol seed, respectively. The present invention uses the first silica sol seed with a larger particle size to mix with the second silica sol seed with a wider particle size distribution to obtain a large particle size bidisperse silica sol with a narrower particle size distribution range, which is beneficial to improve the polishing rate of the polishing liquid product for specific substances, such as copper or silicon dioxide.

[0026] In an embodiment of the present invention, the initial silica sol seed is prepared by reacting an alkaline base liquid and active silicate. The alkaline base liquid is generally prepared from an alkaline substance that acts as a pH regulator. The active silicate is usually obtained by further adding a strong acid to an alkali metal aqueous solution and treating it at a temperature of 25 to 50° C., and then contacting the treated aqueous solution with a strong acid cation exchange resin, or with a strong acid cation exchange resin and a strong base anion exchange resin. The strong acid mentioned herein can be at least one selected from nitric acid, sulfuric acid, phosphoric acid, boric acid, hydrofluoric acid, hydrochloric acid, acetic acid, formic acid, oxalic acid, citric acid, lactic acid, malic acid, gluconic acid, tartaric acid, ethylenediaminetetraacetic acid (EDTA), and diethylenetriaminepentaacetic acid (DTPA).

[0027] In an embodiment of the present invention, the CPS particle size peaks measured by the bidisperse silica sol are respectively recorded as Q1 and Q2, Q1 is the first peak from the left, and Q2 is the second peak from the left, satisfying Q1 / Q2 of 0.65~0.80, preferably 0.65~0.75, and more preferably 0.68~0.75. The CPS particle size peak measured by the bidisperse silica sol satisfies the above conditions, and has a good effect on the grinding selectivity of wafer products containing metals and non-metals while maintaining a high grinding rate, that is, it has a high selectivity for the removal of copper and silicon dioxide. When Q1 / Q2 is lower than 0.65, the grinding rate of copper and silicon dioxide is low, and when Q1 / Q2 is higher than 0.80, the removal selectivity of copper and silicon dioxide is not improved, but the grinding rate of silicon dioxide and copper is reduced.

[0028] The present invention provides a method for preparing a bidisperse silica sol, comprising the following steps: S1. Preparation of alkaline base solution Add 1-10wt% of pH regulator, adjust the pH range to 10.5-12, heat to 90-100°C, keep warm for 1-5h, and obtain alkaline base solution.

[0029] S2. Preparation of active silicic acid Using water glass as raw material, passing through cation exchange resin, diluting to a solid content of 6-8wt%, maintaining the pH at 2-3, to obtain active silicate; S3. Preparation of Bidisperse Silica Sol Add the active silicate of step S2 to the alkaline base liquid of step S1, the reaction temperature is 90-100° C., and an initial silica sol seed with a particle size of 20-35 nm is prepared. At this time, the mass ratio of the alkaline base liquid to the active silicate is 1:(2-7), and the dropping rate of the active silicate is 1-20 g / min, preferably 1-10 g / min, and more preferably 1-5 g / min; Taking initial silica sol seed crystals, adding a pH regulator and dropping active silicic acid therein, respectively, to prepare a first silica sol seed crystal with a particle size of 40-60 nm and a second silica sol seed crystal with a particle size of 40-70 nm; When preparing the first silica sol seed crystal, the reaction temperature is 90-100° C., the mass ratio of the initial silica sol seed crystal to the active silicic acid is 1:(2-10), preferably 1:(3-8), more preferably 1:(3-6), and the pH is 11-12.5; the dripping rate of the active silicic acid is 1-20 g / min, preferably 1-10 g / min, more preferably 3-8 g / min; When preparing the second silica sol seed crystal, the reaction temperature is 90~100°C, the mass ratio of the initial silica sol seed crystal to the active silicic acid is 1:(5~15), preferably 1:(6~13), more preferably 1:(7~12), and the pH is 11~12.5; the dripping rate of the active silicic acid is 1~20g / min, preferably 1~10g / min, and more preferably 2~6g / min.

[0030] S4, mixing the first silica sol seed crystal and the second silica sol seed crystal of step S3, adding a pH regulator, raising the temperature to 90-100° C., and continuously dripping active silicic acid at a dripping speed of 1-5 g / min to obtain a bidisperse silica sol with a particle size of 70-100 nm; The mass ratio of the first silica sol seed crystal and the second silica sol seed crystal to the active silicic acid is 1:(2-8), the pH is maintained at 11-12.5, and the mass ratio of the first silica sol seed crystal to the second silica sol seed crystal is 1:(1-4).

[0031] The pH adjusting agent described in the above preparation method is one or more of sodium hydroxide, potassium hydroxide, sodium silicate water glass, ammonia water, and tetrabutylammonium hydroxide. The pH adjusting agent plays a catalytic reaction role, that is, the pH adjusting agent is an alkaline catalyst. From the viewpoint of suppressing pollution by metal impurities, the alkaline catalyst is preferably at least one of ammonia, tetramethylammonium hydroxide and other ammonium salts. Among them, from the viewpoint of excellent catalytic effect, ammonia is more preferred. Since ammonia is highly volatile, it is easy to remove from silica sol. In addition, the alkaline catalyst can be used alone or in combination of two or more. The lower limit of the content of the alkaline catalyst in the liquid is not particularly limited, but it is considered from the viewpoint of further promoting its role as a hydrolysis catalyst or particle growth, that is, further improving the effect of suppressing the generation of the alkaline catalyst.

[0032] Compared with the existing large-particle silica sol method, the method for preparing bidisperse narrow-distribution silica sol of the present invention has three characteristics of narrow distribution, large-particle size and bidisperse. In the later silicon wafer polishing process, the application of dual-process or multi-process silicon wafers can simultaneously meet the requirements of grinding rate of two or more metals or non-metals. The existing monodisperse narrow-distribution silica sol cannot meet the grinding rate of multiple processes, and two or more silica sols need to be used respectively to meet the polishing of different processes.

[0033] The present invention provides a polishing liquid containing a bidispersed silica sol. The polishing liquid provided by the present invention has the function of increasing the removal rate in the chemical mechanical polishing process of copper and silicon dioxide, and improves the processing efficiency of planarization.

[0034] The present invention is further described in detail below in conjunction with embodiments so that those skilled in the art can implement the invention with reference to the description.

[0035] It should be noted that the experimental methods described in the following embodiments are conventional methods unless otherwise specified, and the reagents and materials can be obtained from commercial channels unless otherwise specified.

[0036] The water glass solution used in the following examples is a commercially available water glass solution product with a mass fraction of 30-40%.

[0037] <Example 1> S1. Preparation of alkaline base solution Add an appropriate amount of 1 wt % sodium hydroxide aqueous solution, adjust the pH to 11, heat to 95° C. and keep warm for 1 hour to obtain an alkaline base solution.

[0038] S2. Preparation of active silicic acid The commercially available water glass solution is diluted to 10wt%, and then passed through a strong acid ion exchange resin column to obtain active silicic acid, which is then diluted to a solid content of 6wt%, and the pH is maintained between 2.1 and 2.5 to obtain active silicic acid.

[0039] S3. Preparation of large particle size bidispersed silica sol 500 g of the active silicic acid obtained in step S2 was added dropwise to 100 g of alkaline base solution at 95° C. for 3 h to obtain initial silica sol seeds with a particle size of 20-35 nm; Take 100g of initial silica sol seed crystals, add sodium hydroxide to adjust the pH to 12, and continue to drop 500g of active silicic acid at 95-100°C for 3h to obtain the first silica sol seed crystals with a particle size between 40-60nm; Take 100g of initial silica sol seed crystals, add sodium hydroxide to adjust the pH to 12, and continue to drop 900g of active silicic acid at 95-100°C for 4h to obtain a second silica sol seed crystal with a particle size between 40-70nm; S4, take 50g of the first silica sol seed crystal and 150g of the second silica sol seed crystal, mix them, add sodium hydroxide to adjust the pH to 12, continue to drop 400g of active silicic acid at 95-100℃, drop for 3h, and obtain a bidispersed silica sol with a particle size of 70~100nm. Its CPS particle size diagram is as follows Figure 1 As shown, SEM Figure 2 shown.

[0040] <Example 2> S1. Preparation of alkaline base solution Add an appropriate amount of 5 wt % ammonia water, adjust the pH to 12, heat to 95° C. and keep warm for 1 h to obtain an alkaline base solution.

[0041] S2. Preparation of active silicic acid The commercially available water glass solution was diluted to 10wt%, then passed through an ion exchange resin column to obtain active silicic acid, which was diluted to a solid content of 6wt% and a pH between 2.1-2.5.

[0042] S3. Preparation of large particle size bidispersed silica sol 500 g of the active silicic acid obtained in step S2 was added dropwise to 100 g of alkaline base solution at 95° C. for 3 h to obtain initial silica sol seeds with a particle size between 20 and 35 nm; Take 100g of initial silica sol seed crystals, add sodium hydroxide to adjust the pH to 12.5, and continue to drop 500g of active silicic acid at 95-100°C for 3h to obtain the first silica sol seed crystal with a particle size between 40-60nm; Sodium hydroxide was added to 100 g of the initial silica sol seed crystal to adjust the pH to 12.5, and 900 g of active silicic acid was continuously added dropwise at 95-100° C. for 4 hours to obtain a second silica sol seed crystal with a particle size of 40-70 nm. S4, take 50g of the first silica sol seed and 100g of the second silica sol seed, mix them, add sodium hydroxide to adjust the pH to 12.5, continue to drop 400 active silicic acid at 95~100℃, drop for 3h, and obtain bidispersed silica sol with a particle size of 70~100nm. Its CPS particle size diagram is as follows Figure 3 As shown, SEM Figure 4 shown.

[0043] <Example 3> S1. Preparation of alkaline base solution Add an appropriate amount of 10wt% sodium silicate, adjust the pH to 11, heat to 95°C for 1 hour, and obtain an alkaline base solution.

[0044] S2. Preparation of active silicic acid The commercially available water glass solution was diluted to 10wt%, then passed through an ion exchange resin column to obtain active silicic acid, which was diluted to a solid content of 6wt% and a pH between 2.1-2.5.

[0045] S3. Preparation of large particle size bidispersed silica sol 400 g of the active silicic acid obtained in step S2 was added dropwise to 100 g of alkaline base solution at 95° C. for 3 h to obtain initial silica sol seeds with a particle size between 20 and 35 nm; Take 100g of initial silica sol seed crystals, add sodium silicate to adjust the pH to 11, and continue to drop 400g of active silicic acid at 95-100°C for 3h to obtain the first silica sol seed crystal with a particle size between 40-60nm; Take 100g of initial silica sol seed crystals, add sodium silicate to adjust the pH to 11, and continue to drop 900g of active silicic acid at 95-100°C for 4h to obtain a second silica sol seed crystal with a particle size between 40-70nm; S4, take 50g of the first silica sol seed crystal and 100g of the second silica sol seed crystal, mix them, add sodium silicate to adjust the pH to 11, continue to drop 500g of active silicic acid at 95~100℃, drop for 3h, and obtain bidispersed silica sol with a particle size of 70~100nm. Its CPS particle size diagram is as follows Figure 5 shown.

[0046] <Example 4> S1. Preparation of alkaline base solution Add an appropriate amount of 1 wt % potassium hydroxide, adjust the pH to 12, heat to 95° C. and keep warm for 1 h to obtain an alkaline base solution.

[0047] S2. Preparation of active silicic acid The commercially available water glass solution was diluted to 10wt%, then passed through an ion exchange resin column to obtain active silicic acid, which was diluted to a solid content of 6wt% and a pH between 2.1-2.5.

[0048] S3. Preparation of large particle size bidispersed silica sol 500 g of the active silicic acid obtained in step S2 was added dropwise to 100 g of alkaline base solution at 95° C. for 3 h to obtain initial silica sol seeds with a particle size between 20 and 35 nm; Take 100g of initial silica sol seed crystals, add potassium hydroxide to adjust the pH to 12, and continue to drop 500g of active silicic acid at 95-100°C for 3h to obtain the first silica sol seed crystal with a particle size between 40-60nm; Take 100g of initial silica sol seed crystals, add potassium hydroxide to adjust the pH to 12, and continue to drop 900g of active silicic acid at 95-100°C for 4h to obtain a second silica sol seed crystal with a particle size between 40-70nm; S4, take 50g of the first silica sol seed crystal and 100g of the second silica sol seed crystal, mix them, add sodium hydroxide to adjust the pH to 12, continue to drop 400g of active silicic acid at 95~100℃, drop for 3h, and obtain bidispersed silica sol with a particle size of 70~100nm. Its CPS particle size diagram is as follows Figure 6 shown.

[0049] <Example 5> The preparation steps are the same as those in Example 1, except that in step S4, 50 g of the first silica sol seed crystal and 50 g of the second silica sol seed crystal are mixed. Figure 7 Shown <Comparative Example 1> The CPS particle size of NN-4060 produced by Hubei Jinwei New Materials Co., Ltd. is shown in the figure below: Figure 8 shown.

[0050] <Comparative Example 2> The CPS particle size of NN-4080 produced by Hubei Jinwei New Materials Co., Ltd. is shown in the figure below: Fig. 9 shown.

[0051] <Comparative Example 3> Step S1 and step S2 are the same as in Example 1, and the subsequent steps are: 500 g of the active silicic acid obtained in step S2 was added dropwise to 100 g of alkaline base solution at 95° C. for 3 h to obtain initial silica sol seeds with a particle size of 20 to 35 nm; 1200 g of active silicic acid was added dropwise to 100 g of initial silica sol seed crystals at 95-100° C. for 8 hours, and 50 g of initial silica sol seed crystals were continuously added to prepare a silica sol solution.

[0052] <Comparative Example 4> The preparation steps are the same as those in Example 1, except that in step S3: 250 g of the active silicic acid obtained in step S2 is mixed with 50 g of alkaline base liquid at 95°C, and then 250 g of the active silicic acid and 50 g of the alkaline base liquid are respectively added dropwise thereto, and the alkaline base liquid and the active silicic acid are added at the same speed to obtain initial silica sol seeds.

[0053] <Comparative Example 5> Step S1 and step S2 are the same as in Example 1. The preparation method of the initial silica sol seed and the first silica sol seed is the same as in Example 1. The subsequent steps are: take 150g of the first silica sol seed, add sodium hydroxide to adjust the pH to 12, continue to drop 400g of active silicic acid at 95-100°C for 3h to prepare a silica sol solution. The CPS particle size diagram of the prepared silica sol solution is as follows: Fig.10 shown. <Evaluation method> The silica sol products of Examples 1 to 5 and Comparative Examples 1 to 5 were used as test objects, and their DLS particle size averages and CPS particle size averages were determined. The silica sol products of Examples 1 to 5 and Comparative Examples 1 to 5 were prepared into polishing liquids, and the polishing rates of Cu and SiO2 polished by the polishing liquids were determined.

[0054] The CPS particle size was tested using a DC24000 UHR high-precision nanoparticle size analyzer; The DLS particle size was tested using a Malvern Zetasizer PRO particle size analyzer; Preparation of polishing liquid: 140 g of silica sol of Examples 1 to 5 and Comparative Examples 1 to 5, 4 g of polyvinyl pyrrolidone, 0.5 g of benzotriazole inhibitor, 1 g of phosphoric acid, 3 g of citric acid, 8 g of hydrogen peroxide, and 840 g of water were respectively mixed to prepare the polishing liquid.

[0055] Polishing liquid grinding rate measurement: the polishing machine is an Ebara machine, the polishing wafer is a silicon wafer loaded with Cu and SiO2 respectively, the polishing pad is a Fujibo pad (H800), the polishing liquid is the polishing liquid prepared in Examples 1 to 5 and Comparative Examples 1 to 5, the flow rate is 150 ml / min, the dresser is a 3M A165P diamond disk, the pressure is 6 lbf, the platen speed is 73 rpm, the carrier speed is 67 rpm, and the polishing head pressure is 1.5 psi. Under the above test conditions, the test wafer is ground, and the removal rate of Cu and SiO2 is calculated from the wear loss, and the unit is (Å / min).

[0056] The results obtained by the above evaluation method are shown in Table 1.

[0057] Table 1 serial number DLS particle size average (nm) CPS particle size average (nm) Difference Q1 Peak Q2 Peak Q1 / Q2 peak ratio <![CDATA[SiO2 removal rate (Å / min)]]> Cu removal rate (Å / min) <![CDATA[SiO2 / Cu removal selectivity]]> Example 1 82.6 75.3 7.3 68 100 0.68 680 1230 0.552 Example 2 86.3 78.4 7.9 72 100 0.72 690 1200 0.575 Example 3 89.5 83.1 6.4 73 100 0.73 720 1220 0.590 Example 4 87.1 79.9 7.2 73 100 0.73 710 1250 0.568 Example 5 88.2 85.3 2.9 78 100 0.78 610 1350 0.452 Comparative Example 1 89.3 60.3 29 / / / 250 900 0.278 Comparative Example 2 88.5 80.1 8.4 / / / 310 800 0.387 Comparative Example 3 72.2 58.4 13.8 / / / 350 820 0.427 Comparative Example 4 81.2 62.8 18.4 / / / 310 830 0.373 Comparative Example 5 75.6 61.3 14.3 / / / 350 870 0.402 from Figures 1 to 7 It can be seen that Examples 1 to 5 are all double-dispersed narrow-distributed silica sols; Figure 8 and Fig. 9 It is known that commercially available sample 1 is a single peak 80nm sample, and commercially available sample 2 is a single peak 60nm sample, which are monodisperse silica sol products; Fig.10 It can be seen that the particle size distribution is not concentrated.

[0058] It can be seen from Table 1 that the polishing liquid prepared by the silica sol products prepared in Examples 1 to 4 has a good removal rate for Cu and SiO2. It can be seen from Example 5 that adjusting the addition ratio of the first silica sol seed crystal and the second silica sol seed crystal can affect the selectivity of the polishing liquid prepared by the silica sol product for Cu and SiO2, reduce the removal rate of SiO2, and increase the removal rate of Cu.

[0059] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes. They can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to the specific details and the embodiments shown and described herein.

Claims

1. A bidispersed silica sol for chemical mechanical polishing, characterized in that: The bidisperse silica sol is formed by mixed growth of a first silica sol seed with a particle size of 40-60 nm and a second silica sol seed with a particle size of 40-70 nm. The particle size of the bidisperse silica sol is 70-100 nm, and the difference between the DLS particle size average and the CPS particle size average of the bidisperse silica sol is between 0-10 nm.

2. A bidisperse silica sol, characterized in that: The bidisperse silica sol is formed by mixed growth of a first silica sol seed with a particle size of 40-60 nm and a second silica sol seed with a particle size of 40-70 nm. The particle size of the bidisperse silica sol is 70-100 nm, and the difference between the DLS particle size average and the CPS particle size average of the bidisperse silica sol is between 0-10 nm.

3. The bidisperse silica sol according to claim 1 or 2, characterized in that: The bidispersed silica sol is formed by mixing a first silica sol seed crystal with a particle size of 40-60 nm and a second silica sol seed crystal with a particle size of 40-70 nm, and then adding a pH regulator and dropping active silicic acid to prepare the growth.

4. The bidisperse silica sol according to claim 3, characterized in that: The first silica sol seed crystal is prepared by adding a pH regulator and dropping active silicic acid for a first time length to an initial silica sol seed crystal with a particle size of 20 to 35 nm to grow; The second silica sol seed crystal is prepared and grown by adding a pH regulator and dropping active silicic acid for a second time length into an initial silica sol seed crystal with a particle size of 20-35 nm.

5. The bidisperse silica sol according to claim 1 or 2, characterized in that: The CPS particle size peaks measured by the bidisperse silica sol are respectively recorded as Q1 and Q2, and Q1 / Q2 is 0.65-0.

80.

6. The method for preparing bidisperse silica sol according to claim 1 or 2, characterized in that: The method comprises the following steps: mixing a first silica sol seed crystal with a particle size of 40-60 nm and a second silica sol seed crystal with a particle size of 40-70 nm, adding a pH regulator, and dropping active silicic acid to obtain a bidispersed silica sol with a particle size of 70-100 nm.

7. The method for preparing bidisperse silica sol according to claim 6, characterized in that: The first silica sol seed crystal is prepared by adding a pH regulator and dropping active silicic acid for a first time length to an initial silica sol seed crystal with a particle size of 20 to 35 nm to grow; The second silica sol seed crystal is prepared by adding a pH regulator and dropping active silicic acid for a second time length to an initial silica sol seed crystal with a particle size of 20 to 35 nm to grow; The initial silica sol seed crystals are formed by dropping active silicate into an alkaline base solution, and the particle size of the initial silica sol seed crystals is 20-35 nm; The preparation method of the alkaline base liquid is as follows: adding 1-10 wt% of a pH regulator, adjusting the pH range to 10.5-12, heating to 90-100° C., and keeping the temperature for 1-5 hours to obtain; The preparation method of the active silicate is as follows: using water glass as a raw material, and diluting it after passing through a cation exchange resin; The reaction temperature when preparing the initial silica sol seed crystal, the first silica sol seed crystal, the second silica sol seed crystal and the bidisperse silica sol is 90-100°C.

8. The method for preparing bidisperse silica sol according to claim 6, characterized in that: When preparing the initial silica sol seed crystals, the mass ratio of the alkaline base liquid to the active silicic acid is 1:(2-7); When preparing the first silica sol seed crystals, the mass ratio of the initial silica sol seed crystals to the active silicic acid is 1:(2-10), and the pH is 11-12.5; When preparing the second silica sol seed crystals, the mass ratio of the initial silica sol seed crystals to the active silicic acid is 1:(5-15), and the pH is 11-12.5; When preparing the bidisperse silica sol, the mass ratio of the first silica sol seed and the second silica sol seed to the active silicic acid is 1:(2-8), the pH is 11-12.5, and the mass ratio of the first silica sol seed to the second silica sol seed is 1:(1-4).

9. The method for preparing bidisperse silica sol according to claim 6, characterized in that: The drop rate of the active silicate is 1-20 g / min; When preparing the initial silica sol seed crystals, the drop rate of the active silicic acid is 1-5 g / min; When preparing the first silica sol seed crystal, the drop rate of the active silicic acid is 3-8 g / min; When preparing the second silica sol seed crystal, the dropping rate of the active silicic acid is 2-6 g / min; When preparing the bidisperse silica sol, the dropping rate of the active silicic acid is 1-5 g / min.

10. A polishing liquid for chemical mechanical polishing of copper and silicon dioxide, comprising the bidisperse silica sol according to claim 1 or 2 and the bidisperse silica sol prepared by the preparation method according to claim 6.

Citation Information

Patent Citations

  • Monodisperse large-grain-diameter and high-stability acid silica sol and preparation method thereof

    CN102432027B

  • A method for preparing large-particle-size silica sol

    CN105883824B